The effect of acupuncture on exam anxiety in medical students: a randomized crossover study - Baesso Cavalca, Alexandre Matheus [UNESP] (2019)
Objective: Acupuncture (AC) has been used for treatment of chronic and pre- operative anxiety. However, no study has evaluated the effect of AC on exam anxiety in undergraduate students. The aim of this study was to evaluate whether AC reduces pre-examination anxiety compared to placebo (PL) and non- intervention (NI). Methods: Twenty students from the first terms of physiotherapy and dentistry courses were randomized to receive AC, PL and NI in a crossover manner and subsequently completed three anatomy exams with an interval of 1 month between exams/interventions. AC was performed on acupoints PC-6 (Neiguan), HT-7 (Shenmen), LV-3 (Taichong) and Yintang one day prior to each exam. The PL was performed outside the meridians and the needles were inserted superficially without obtaining De Qi. Levels of anxiety were measured using a visual analogue scale before and after each intervention as well as before each exam. Results: Anxiety levels were reduced after AC and PL intervention compared to NI on the day before the exam, as well as on the day of the exam. Conclusion: These results suggest that AC can be used as an anxiolytic method in students under conditions of situational stress.